Revenge Porn: Digital Crimes and Implications for Victims - Zico Junius Fernando; Papontee Teeraphan; Jaco Barkhuizen; Agusalim Agusalim (Kosmik Hukum, 2023)
In today's digital era, problems related to cybercrime are increasing, one of which is "Revenge Porn". Revenge porn refers to deliberately distributing pornographic content without the consent of the person seen in the content, often done by ex-spouses as a form of revenge. Due to the easy access and dissemination of information through the internet, revenge porn has become a threat to many individuals, especially women. Victims of this act often face social stigmatization, isolation, and depression. The stigma attached to victims affects their social and work lives, hampering their opportunities in many aspects of life. This research utilizes normative legal methods by adopting statutory, conceptual, comparative, and futuristic approaches. The nature of this research is descriptive-prescriptive. The data that has been collected is analyzed using the content analysis method. This research results in that apart from psychological and social impacts, and revenge porn also has legal implications. Some countries have responded by implementing specific laws to address this issue, but the challenge is distinguishing between the right to freedom of expression and invasion of privacy. Understanding this issue is essential for victims and society to build awareness and prevent the spread of this kind of digital crime. People can protect themselves and others from the dangers of revenge porn with proper understanding and preventive measures.Keywords: Revenge Porn, Digital Crime, Psychological Impact, Social Stigmatization.